2018
DOI: 10.1016/j.thromres.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A dichotomy in platelet activation: Evidence of different functional platelet responses to inflammatory versus haemostatic stimuli

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
0
16
0
4
Order By: Relevance
“…Activation of platelets or leucocytes led to PLA formation [ 50 ]. Biochemic substances associated with thrombosis, such as adenosine diphosphate (ADP), collagen, platelet-activating factor (PAF), and thrombin enhanced PLA level versus lack of stimulation [ 5 , 36 , 50 ]. Similarly, proinflammatory N-formyl-methionyl-leucyl-phenylalanine (fMLP), serotonin, and stromal cell-derived factor-1α (CXCL12) increased PLA formation versus lack of stimulation, but this effect was lower than induced by prothrombotic agents.…”
Section: Characteristics Of Platelet–leucocyte Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of platelets or leucocytes led to PLA formation [ 50 ]. Biochemic substances associated with thrombosis, such as adenosine diphosphate (ADP), collagen, platelet-activating factor (PAF), and thrombin enhanced PLA level versus lack of stimulation [ 5 , 36 , 50 ]. Similarly, proinflammatory N-formyl-methionyl-leucyl-phenylalanine (fMLP), serotonin, and stromal cell-derived factor-1α (CXCL12) increased PLA formation versus lack of stimulation, but this effect was lower than induced by prothrombotic agents.…”
Section: Characteristics Of Platelet–leucocyte Aggregatesmentioning
confidence: 99%
“…PLA are defined as heterotypic combinations of at least one platelet with one leucocyte [ 4 ]. PLA are formed during immune or thrombotic reactions [ 5 ]. Hence, PLA have been investigated as potential biomarkers in many pathologies, including chronic obstructive pulmonary disease [ 6 ], antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis [ 7 ], consumptive coagulopathy in xenotransplantation [ 8 ], cutaneous Arthus reactions [ 9 ], and infections [ 10 ]-among others COVID-19 [ 11 ]-and sepsis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 A) and PMN-platelet heteroaggregate formation (Fig. 1 B 38 ), which resulted in the increased amount of PMNs in thrombi. PMN attraction to the growing thrombi observed here has been previously demonstrated in vivo for another TLR4 agonist HMGB1 39 .…”
Section: Discussionmentioning
confidence: 97%
“…Platelets play a key role in the inflammatory response. [14][15][16] However, the role of P-selectin in systemic inflammation requires further investigation. We also evaluated other traditional risk factors and showed that BMI, TC, and TG were all increased and HDL-C was decreased in patients with CHD compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets play a key role in the inflammatory response. 14 16 However, the role of P-selectin in systemic inflammation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%